First record of desmoncus mart. (arecaceae) in São Paulo State, Brazil - Ferraz, Tamylle Aparecida Pereira [UNESP]; Seidinger, Letícia Chedid [UNESP]; Teixeira, Wilton Felipe; Udulutsch, Renata Giassi [UNESP] (Pensoft Publishers, 2019)
Desmoncus leptoclonos Drude is recorded for the first time for the state of São Paulo, Brazil. Based on this new record, the geographical distribution of Desmoncus Mart. for Brazil is expanded. An identification key to climbing species of Brazilian Desmoncus, a description, a map of geographic distribution, photographs, and comments concerning Desmoncus leptoclonos are provided.
Keywords: Desmoncus leptoclonos; Parque Estadual do Morro do Diabo; Semideciduous seasonal forest